HUBUNGAN FREKUENSI ANTENATAL CARE (ANC) DENGAN PEMILIHAN PENOLONG PERSALINAN DI WILAYAH KERJA PUSKESMAS MOYO HULU KABUPATEN SUMBAWA TAHUN 2013 - Suwanti Suwanti; Sri Romiastuti; Anak Agung Sagung Putri Chandradewi (poltekkes kemenkes mataram, 2014)
Abstract: Nationally, the percentage of first visit (K1) of 95.26 % , and fourth visits (K4) of 85.56 % , the number of visits has reached the national targets of 80 % but still there is a mother who births assisted by trained non- health by 40 , 2 % and births attended by health personnel as much as 95.26 % . The purpose of this study was to analyze the frequency relationship Antenatal Care (ANC) with the selection of skilled attendants in the Work Area Health Center Moyo Hulu Sumbawa District in 2013.This study used observational analytic design , while in terms of cross-sectional nature of time . The population in this study were all pregnant women in the Work Area Health Center Moyo Hulu as many as 98 pregnant women . Systematic sampling technique using random sampling with a sample size of 79 pregnant women . Analyzed using Chi Square.The results showed that the majority of pregnant women with gestational age-appropriate number of visits as many as 53 people (67.1 %) and a fraction with the number of visits is not appropriate gestational age by 26 people (32.9 %) , the majority of pregnant women choose power healthcare delivery that will help as many as 50 people (63.3 %) and a small portion of pregnant women choose non health workers (birth attendants) as many as 29 people (36.7%). While the results of statistical tests showed p = 0.000 < α = 0.05 ( 0.000 < 0.05) so that it can be concluded that there is a frequency of Antenatal Care ( ANC ) with the selection of skilled attendants in the Work Area Health Center Moyo Hulu Sumbawa District in 2013.